The effectiveness of the robotic game kit on anxiety among hospitalized preschool children: A non-randomized controlled trial - Sima Pourteimour; Sahar Kazemi (Tehran University of Medical Sciences, 2021)
Background & Aim: Hospitalization is a challenging experience all children go through in their life, which leads to their utmost anxiety. In this sense, interactive games and activities can help ease this psychological burden. Therefore, we endeavored to determine the effectiveness of a robotic game kit (RGK) on the anxiety of hospitalized preschoolers. Methods & Materials: This non-randomized controlled clinical trial was conducted in a pediatric hospital, Iran between March and July 2019. 59 participants were assigned to intervention (n=30) or control (n=29) groups through available sampling. Inclusion criteria were Iranian native children aged 3-7 years with communication ability. The RGK was applied in eight sessions at least seven consecutive days of hospitalization. The collected data by using the demographic information form and the preschool anxiety scale (PAS) were analyzed in descriptive, chi-square, t-test, the one-way ANCOVA (analysis of covariance), and multivariate analysis of covariance (MANCOVA). Results: Two groups were homogenous in terms of demographic variables (p>0.05). There was no statistically significant difference between the mean score of PAS before the intervention in the intervention 46.33±15.81 and control groups 37.24±19.65 (p=0.055). the mean score of PAS in the intervention group was significantly lower compared to the control groups (P=0.030). Also, using the RGK was effective in two subscales related to separation anxiety and physical injury fears  (P=0.034). Conclusion: The modern RGKs could have a significant place in pediatric health care in hospitals. It is thus an undeniable fact that high-quality comprehensive care can be boosted through RGK based interventions for children encountering stressful situations.